2016
DOI: 10.1037/tra0000033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how deployment experiences change over time: Comparison of female and male OEF/OIF and Gulf War veterans.

Abstract: Despite increased attention to the evolving nature of war, the unique challenges of contemporary deployment, and women's changing role in warfare, few studies have examined differences in deployment stressors across eras of service or evaluated how gender differences in deployment experiences have changed over time. Using data collected from two national survey studies, we examined war cohort and gender differences in veterans' reports of both mission-related and interpersonal stressors during deployment. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Studies have shown that veterans deployed to combat zones are often at risk for posttraumatic stress disorder (PTSD), depression, substance use disorders, and other mental health problems (Fox et al, 2016; Hoge, Auchterlonie, & Milliken, 2006; Milliken, Auchterlonie, & Hoge, 2007; Reger et al, 2015). Recently, attention has been paid to postdeployment experiences, their association with social connections, social support, and how these factors affect mental health outcomes and service use (Adler & Castro, 2013; Mustillo et al, 2015; Pietrzak, Johnson, Goldstein, Malley, & Southwick, 2009; Smith, Benight, & Cieslak, 2013; Sripada, Lamp, Defever, Venners, & Rauch, 2016; Tsai, Harpaz-Rotem, Pietrzak, & Southwick 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that veterans deployed to combat zones are often at risk for posttraumatic stress disorder (PTSD), depression, substance use disorders, and other mental health problems (Fox et al, 2016; Hoge, Auchterlonie, & Milliken, 2006; Milliken, Auchterlonie, & Hoge, 2007; Reger et al, 2015). Recently, attention has been paid to postdeployment experiences, their association with social connections, social support, and how these factors affect mental health outcomes and service use (Adler & Castro, 2013; Mustillo et al, 2015; Pietrzak, Johnson, Goldstein, Malley, & Southwick, 2009; Smith, Benight, & Cieslak, 2013; Sripada, Lamp, Defever, Venners, & Rauch, 2016; Tsai, Harpaz-Rotem, Pietrzak, & Southwick 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that younger veterans have higher rates of mental health problems compared to older veterans from the same warzone (Seal et al, 2007). The wars in Iraq and Afghanistan also may be more stressful because of multiple war-zone tours, high combat exposure, and longer deployments compared to earlier wars (Fox et al, 2016). Other traumatic events such as having a history of childhood abuse or neglect also increase the likelihood of mental health problems postdeployment (Cabrera, Hoge, Bliese, Castro, & Messer, 2007; LeardMann, Smith, & Ryan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent conflicts in Iraq and Afghanistan, where there are no clear frontlines, women have been increasingly exposed to combat. 6 Women veterans are sustaining injuries and returning with deploymentconnected medical conditions similar to, and in some cases with greater frequency, than their male counterparts such as traumatic brain injury, traumatic amputation, and posttraumatic stress disorder (PTSD). 7 In 2013, the rule restricting women from certain operations, including combat arms specialties, was rescinded by the Department of Defense, thus officially recognizing and allowing women to serve in combat zones.…”
Section: Who Are Women Veterans?mentioning
confidence: 99%
“…How to take a military history. 6. Essential role of women's health specialists in enhancing health systems and providing care to women veterans.…”
mentioning
confidence: 99%
“…Veterans of the recent wars in Iraq and Afghanistan report experiencing toxic exposures, although they generally report fewer exposures than veterans of the first Gulf War [27,28]. The VA recognizes that veterans were exposed to these hazards in theater, including: burn pits, depleted uranium, chemical warfare agents, and exposure to work related chemicals, among others [29].…”
Section: Introductionmentioning
confidence: 99%